STUDENTS' PERCEPTION OF THE USE OF SYAM-OK IN THE LEARNING PROCESS - Waliana, Andi Bunga; Jabu, Baso; Tahir, Muh. (Universitas Negeri Makassar, 2022)
Universitas Negeri Makassar is a university that implements bold learning by launching the Open Knowledge System and Application Management Application (SYAM-OK). This study aims to determine students' perceptions of the use of SYAM-OK in learning. Three aspects are measured on student perceptions of using SYAM-OK in learning, namely: Learning Process, Capability (Lecturer Competency), and Learning Effectiveness. Researchers apply a mix of quantitative and qualitative methods to achieve research objectives. The data collected was in the form of a Like questionnaire using Google Forms and interviews. The subjects of this study were students of the English Language Education Study Program class of 2020. The sample for the questionnaire was 60 students and the interviews for 8 students were taken using a voluntary sampling technique. The results of the data analysis showed that (1) students' perceptions about the use of SYAM-OK in learning with the classification of 29% of students classified as very positive, 51% of students classified as positive, and 20% of students classified as neutral and no students had negative and very negative perceptions. (2) The results of interviews with students show that the use of SYAM-OK in learning is positive. Therefore, it can be concluded that students use SYAM-OK in effective learning.